2020
DOI: 10.1088/2053-1591/ab62fb
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-static compression characterization of binary nanoclay/graphene reinforced carbon/epoxy composites subjected to seawater conditioning

Abstract: Fiber reinforced polymer composite (FRPC) materials are superior to other conventional materials because of their high strength to weight ratio, corrosion resistance, and moisture resistance. FRPC materials are preferred in many high-end applications such as marine, automobile, aerospace, and advanced sporting goods. The aim of this study was to investigate the in-plane quasi-static compressive and durability studies of nanophased FRPC materials. Composite samples were fabricated using unmodified epoxy and epo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…[19][20][21] In addition, high aspect ratio of GnPs along with presence of functional groups on their surface increase fibre-matrix interaction and hence improve interfacial bonding. [22][23][24][25][26] However, the use of increased amount of GnPs degrades mechanical properties because of the nanoparticles' agglomeration. [27][28][29][30][31] Though significant researches have been carried out to study the mechanical properties of GnPs-polymer composites, the study on the mechanical properties of GnP added FRPs is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] In addition, high aspect ratio of GnPs along with presence of functional groups on their surface increase fibre-matrix interaction and hence improve interfacial bonding. [22][23][24][25][26] However, the use of increased amount of GnPs degrades mechanical properties because of the nanoparticles' agglomeration. [27][28][29][30][31] Though significant researches have been carried out to study the mechanical properties of GnPs-polymer composites, the study on the mechanical properties of GnP added FRPs is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles as a secondary reinforcement tend to improve the mechanical and thermal properties of matrix material as well as improve the interfacial bond between fiber and matrix [3]. Various organic and inorganic nanoparticles have been investigated by many researchers [4]. Even a small percentage of nanoparticle addition significantly influences mechanical properties of FRPC materials [5].…”
Section: Effect Of Salt Fog Spray and Ultraviolet Exposure On The Framentioning
confidence: 99%
“…Among several approaches to achieve this objective, addition of nanoparticles in the epoxy matrix has been considered to be the most promising to improve transverse mechanical properties in the FRPCs. 8,16 Green et al added carbon nanofibers (CNFs) in epoxy matrix and observed 20% and 26% increased flexural strength and modulus of CFRPCs, respectively. 17 Addition of AlO 2 and TiO 2 nanoparticles significantly improved fatigue crack resistance of the epoxy matrix.…”
Section: Introductionmentioning
confidence: 99%